МУСИҚАНИНГ ТАРБИЯВИЙ АҲАМИЯТИ ВА ЎЗБЕК МУМТОЗ МУСИҚА САНЪАТИ - Романова, С. (SCIENCE and SOCIETY, 2020)
The article is of a great importance for future teachers in music, because it contains valuable information how to create classical works of a high artistic level and perform them. It is one of the main factors of successful teaching, the author also describes the ways of performing classical works, requirements to the qualification and skill.